Sugarcane–Peanut Intercropping System Enhances Bacteria Abundance, Diversity, and Sugarcane Parameters in Rhizospheric and Bulk Soils - Pang, Ziqin; Fallah, Nyumah; Weng, Peiying; Zhou, Yongmei; Tang, Xiumei; Tayyab, Muhammad; Liu, Yueming; Liu, Qiang; Xiao, Yijie; Hu, Chaohua; Kan, Yongjun; Lin, Wenxiong; et al. (Frontiers in Microbiology, 2022)
Sugarcane-legume intercropping systems can effectively control pests and diseases as well as improve the fertility and health of farmland soil. However, little is known about the response of bacterial abundance, diversity, and community composition in the rhizosphere and non-rhizosphere soils under sugarcane-peanut farming system. A field experiment was conducted with two treatments: sugarcane monoculture and sugarcane-peanut intercropping to examine the response of sugarcane parameters and edaphic factors. We also deciphered bacterial abundance, diversity and community composition in the root endosphere, rhizosphere and bulk soil by leveraging Illumina sequencing to conduct the molecular characterization of the 16S rRNA gene and nitrogenase (nifH) gene. We observed that sugarcane-peanut intercropping exhibited the advantages of tremendously increasing cane stalk height, stalk weight and available stalk number, and edaphic factors, namely, pH (1.13 and 1.93), and available phosphorus (AP) exhibited a fourfold and sixfold increase (4.66 and 6.56), particularly in the rhizosphere and bulk soils., respectively. Our result also showed that the sugarcane-peanut intercropping system significantly increased bacterial richness of 16S rRNA gene sequencing data by 13.80% and 9.28% in the bulk soil and rhizosphere soil relative to those in the monocropping sugarcane system, respectively. At the same time, sugarcane intercropping with peanuts significantly increased the Shannon diversity of nitrogen fixing bacteria in the sugarcane rhizosphere soil. Moreover, most edaphic factors exhibited a positive regularity effect on bacterial community composition under the intercropping system. LEfSe analysis of the 16S rRNA sequencing data revealed that bacteria in the root endosphere of the intercropped cane proliferated profoundly, primarily occupied by Devosia, Rhizobiales, Myxococcales, Allorhizobium-Neorhizobium-Pararhizobium-Rhizobium, Bradyrhizobium and Sphingomonas. In conclusion, our findings demonstrated that sugarcane-peanut intercropping can enhance edaphic factors, sugarcane parameters and bacterial abundance and diversity without causing adverse impact on crop production and soil.